1995
DOI: 10.1128/aac.39.6.1243
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CP-99,219, a new fluoroquinolone, for treatment of experimental penicillin- and cephalosporin-resistant pneumococcal meningitis

Abstract: CP-99,219 is a new fluoroquinolone that has excellent activity against gram-positive organisms including penicillin-and cephalosporin-resistant Streptococcus pneumoniae strains. In our well-established rabbit model of meningitis, we conducted experiments to determine the concentrations of CP-99,219 in cerebrospinal fluid (CSF) after intravenous administration and its ability to eradicate two penicillin-resistant pneumococcal isolates. The peak and trough concentrations of CP-99,219 in the CSF were from 19 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…The S. pneumoniae strains used in the acute infection and pneumonia models were susceptible to penicillins and macrolides, but it is expected that trovafloxacin will have equivalent activity against strains resistant to these antibiotics since recent in vitro data have shown trovafloxacin to be equally potent against penicillin-macrolide-susceptible and -resistant S. pneumoniae strains (19,25). When trovafloxacin was evaluated for therapy of experimental meningitis caused by a penicillin-and cephalosporin-resistant S. pneumoniae strain, the effectiveness of the compound was comparable to that of other antibiotics, such as vancomycin and ceftriaxone, and therapy with trovafloxacin resulted in a significant reduction of bacterial populations of penicillin-resistant organisms in cerebrospinal fluid (26).…”
Section: Discussionmentioning
confidence: 99%
“…The S. pneumoniae strains used in the acute infection and pneumonia models were susceptible to penicillins and macrolides, but it is expected that trovafloxacin will have equivalent activity against strains resistant to these antibiotics since recent in vitro data have shown trovafloxacin to be equally potent against penicillin-macrolide-susceptible and -resistant S. pneumoniae strains (19,25). When trovafloxacin was evaluated for therapy of experimental meningitis caused by a penicillin-and cephalosporin-resistant S. pneumoniae strain, the effectiveness of the compound was comparable to that of other antibiotics, such as vancomycin and ceftriaxone, and therapy with trovafloxacin resulted in a significant reduction of bacterial populations of penicillin-resistant organisms in cerebrospinal fluid (26).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental agents such as the fluoroquinolones, CP-99,219 (13,51) and clinafloxacin (29), and biapenem (57) have been shown to have excellent in vitro activities against penicillin-resistant strains. Clinafloxacin and CP-99, 219 were effective in reducing rapidly the bacterial concentrations in CSF in a model of experimental meningitis (17,49). No clinical data are available to confirm these observations.…”
Section: Therapy For Meningitis: Clinical Experience and Animal Studiesmentioning
confidence: 98%
“…Because of their excellent antibacterial activity and favorable CSF penetration, the new fluoroquinolones (e.g., trovafloxacin, gatifloxacin, and moxifloxacin) have been shown to be effective for treatment of resistant pneumococcal meningitis in rabbits (9,12,15). We demonstrated that BMS-284756 is highly active against cephalosporin-resistant S. pneumoniae in this meningitis model.…”
Section: Discussionmentioning
confidence: 76%